Material didático digital: do papel à tela como proposta pedagógica bilíngue para alunos surdos. - Viudes, Ariadne Haak (Universidade Federal de São Carlos, 2023)
Historically, the education of the deaf has been permeated with conflicts and controversies. Although there is a growth in scientific research in the sense of producing educational references for this minority group, the methods and methodologies applied are recurrently subjected to oral practices, overvaluing the Portuguese language, relegating sign language to a supporting role in the students' teaching-learning processes deaf. The present work aims to analyze digital and bilingual teaching materials for the deaf available in digital media, pointing out the potential and plurality of multimodal and semiotic resources. Using descriptive and exploratory analysis methodologies, the tools used in four selected digital and bilingual teaching materials were analyzed, which have the deaf as their target audience, materials that are available through streaming, highlighting the potential and plurality of multimodal and semiotic resources in the contribution to the production and implementation in order to promote quality in bilingual education for deaf students. It considers the many possibilities of reinventing, through technological resources, the didactic materials available to students in the path of practices and learning opportunities for students in school phase.
Digital teaching material: from paper to screen as a bilingual pedagogical proposal for deaf students.
Keywords: Surdos; Educação Bilíngue; Material Didático Digital; Multimodalidade; Deaf People; Bilingual Education; Digital Teaching Material; Multimodality; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO